THE PROMOTION OF LIFE QUALITY OF VULNERABLE GROUPS IN KRUNGYAN, TUNGYAI DISTRICT, NAKHON SI THAMMARAT PROVINCE - Kittitharo (Thuetong), Phra Surachet; Nunklam, Direk; Phrakhru Wiratthammachot (Journal of MCU Nakhondhat, 2024)
The objectives of this research article are 1) to study the promotion of quality of life of Vulnerable people In the area of ​​Krungyan Subdistrict Thung Yai District Nakhon Si Thammarat Province and 2) to study recommendations for promoting the quality of life of vulnerable groups of people. In the area of ​​Krungyan Subdistrict Thung Yai District Nakhon Si Thammarat Province It is a combined method research. Quantitative research Data were collected using questionnaires from a sample group of 183 people residing in Krungyan Subdistrict and qualitative research. Data were collected by interviewing 20 key informants. The results of the research found that: 1) Promoting the quality of life of vulnerable groups of people In the area of ​​Krungyan Subdistrict Thung Yai District, Nakhon Si Thammarat Province, overall has an average of the results. is at a moderate level ( = 3.25) when considered as Each aspect was sorted by average from high to low. It was found that the residential aspect The average value was highest ( = 3.38), followed by the mental aspect ( = 3.25) and access to welfare and government services ( = 3.23), social relationships ( = 3.22), and the physical aspect. has the lowest average ( = 3.15) 2) Suggestions on promoting the quality of life of vulnerable people in Krungyan Subdistrict. Physical aspect: It was found that physical fitness should be promoted. Access to health care, nutrition, exercise, medical treatment, and mental aspects were found to promote relationships. stress management and find balance to make life meaningful full of happiness and positive attitude Regarding housing, it was found that living together like relatives should be promoted. In terms of social relations, it was found that it should be promoted. Have positive and responsive interactions with others, with family and friends. In terms of access to welfare and services, the government found that social justice should be promoted. equal opportunity